LEGAL REVIEW OF DRUG DISPENSING BY DOCTORS AND PHARMACEUTICAL PROVISIONS CONCERNING DRUG SUPPLY AND STORAGE - Yeni Nuraeni (INFOKUM, 2022)
The Indonesian legal system does not regulate the implementation of drug dispensing, so these conditions cause difficulties in practice. A doctor who performs drug dispensing, it becomes unclear his position. The purpose of this study was to find out an overview of the provision, storage of drugs, and dispensing of drugs, and provisions regarding the provision, storage of drugs, and dispensing of drugs by doctors. This research is an analytical descriptive using a normative approach. The results of the study explained that the procurement, service and distribution of drugs can only be carried out by pharmaceutical personnel. Doctors have the authority to carry out drug dispensing activities, namely storing and dispensing and dispensing medicines to patients directly if they meet the requirements as stipulated by laws and regulations, namely doctors who practice in remote areas where there are no pharmacies.